MENTAL HEALTH SCREENING TOOLS AMONG MALE JUVENILE OFFENDERS IN INCARCERATED JUVENILE: A LITERATURE REVIEW - Prasetyo Aji Nugroho; Somporn Rungreangkulkij (UNEJ e-Proceeding, 2022)
Background: Juveniles will have high levels of mental health problems during incarceration. The prevalence of mental health problems in male adolescents increases conduct disorder risk. Additionally, male juvenile offenders, possibility, will have a psychotic illness, major depression, ADHD, and PTSD. A previous study reported that male juveniles incarcerated experience psychological distress: sleep disturbance, depression, hostility, inferiority, and anxiety. The increasing frequency of mental health problems in incarcerated juveniles begins with mental health screening. Screening aims to recognize high-risk juvenile offenders who need medical care and those requiring further assessment. Purpose: This study aims to describe the mental health screening tool among male juvenile offenders in incarcerated juveniles. Methods: The method of this study is a literature review. Results: There are many mental health screenings for incarcerated across the world. Each country has a standard to measure mental health problems using mental health screening. Considerations for mental health screening are ease of access, time and cost-effectiveness, and cross-cultural validity. Conclusion: This review will illustrate the significance of mental health awareness among male juvenile offenders. Therefore, the psychiatric and mental health nurse is essential in caring for incarcerated male juvenile offenders.